2017
DOI: 10.1007/s00264-017-3436-z
|View full text |Cite
|
Sign up to set email alerts
|

Hip fusion takedown to a total hip arthroplasty—is it worth it? A systematic review

Abstract: Takedown of a fused-hip can be a challenging procedure. Although patients can benefit functionally, both patients and surgeons need to be aware of the complications and increased risk of further revision procedures, which should be an important part of the pre-operative discussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 38 publications
1
28
1
Order By: Relevance
“…Conversely, the rate of intra-operative complication was very low; e.g., no intra-operative fracture was observed. This is in contradiction with recent literature results [31,32], and we hypothesise that the use of custom prothesis designed to fit perfectly with intramedullary anatomy may explain those differences.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Conversely, the rate of intra-operative complication was very low; e.g., no intra-operative fracture was observed. This is in contradiction with recent literature results [31,32], and we hypothesise that the use of custom prothesis designed to fit perfectly with intramedullary anatomy may explain those differences.…”
Section: Discussioncontrasting
confidence: 99%
“…Sochart and Porter [34] reported good long-term results of Charnley total hip replacement in patients with spontaneous fusion by ankylosing spondylitis. In their series, the probability that both components would survive was 91% at ten years, 73% at 20 years, and 70% at 30 years [32]. However, in two reports at 7- [4] and ten year [8] follow-up, the rates of failure were high, particularly in younger patients and in patients who had one or more previous operations.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Therefore, patients seek conversion to THA, hoping to alleviate symptoms. However, a systematic review by Jauregui et al described that specific postoperative complications were 5.3% for infection, 4.7% for nerve-related complications, 2.6% for instability, 6.2% for loosening, 13.1% for abductor-related complications, and 1.2% for venous thrombotic events [22]. Another study by Richards and Duncan reported significantly worse clinical outcomes and patient satisfaction as well as higher complication rates compared to common primary and revision THA [23].…”
Section: Discussionmentioning
confidence: 99%
“…Another study by Richards and Duncan reported significantly worse clinical outcomes and patient satisfaction as well as higher complication rates compared to common primary and revision THA [23]. Regardless of the higher complication rate, patient satisfaction and postoperative outcomes were generally good [6,8,22]. Regarding surgical techniques, it was difficult to secure adequate visualization of the surgical field due to the contracture of the soft tissue and a lack of hip movement [7,21].…”
Section: Discussionmentioning
confidence: 99%